Novel Combined Tissue Transcriptome Analysis After Lentogenic Newcastle Disease Virus Challenge in Inbred Chicken Lines of Differential Resistance - Deist, Melissa S.; Gallardo, Rodrigo A.; Dekkers, Jack C. M.; Zhou, Huaijun; Lamont, Susan J. (Frontiers in Genetics, 2020)
Disease has large negative impacts on poultry production. A more comprehensive understanding of host-pathogen interaction can lead to new and improved strategies to maintain health. In particular, host genetic factors can lead to a more effective response to pathogens, hereafter termed resistance. Fayoumi and Leghorn chicken lines have demonstrated relative resistance and susceptibility, respectively, to the Newcastle disease virus (NDV) vaccine strain and many other pathogens. This biological model was used to better understand the host response to a vaccine strain of NDV across three tissues and time points, using RNA-seq. Analyzing the Harderian gland, trachea, and lung tissues together using weighted gene co-expression analysis (WGCNA) identified important genes that were co-expressed and associated with parameters including: genetic line, days post infection (dpi), challenge status, sex, and tissue. Pathways and driver genes, such as EIF2AK2, MPEG1, and TNFSF13B, associated with challenge status, dpi, and genetic line were of particular interest as candidates for disease resistance. Overall, by jointly analyzing the three tissues this study identified genes and gene networks that led to a more comprehensive understanding of the whole animal response to lentogenic NDV than that obtained by analyzing the tissues individually.